Sinusoidal obstruction syndrome in a paediatric patient with acute lymphoblastic leukaemia after completion of reinduction therapy according to ALL Intercontinental Berlin-Frankfurt-Münster 2009 - Pawlik-Gwozdecka, Dorota; Irga-Jaworska, Ninela; Tomaszewski, Marek; Adamkiewicz-Drożyńska, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2018)
Sinusoidal obstruction syndrome (SOS), also termed veno-occlusive disease (VOD) of the liver, is a well-known complication of haematopoietic stem cell transplantation (HSCT) both in children and adults. In the medical literature there are occasional reports of SOS in patients receiving conventional chemotherapy. In children with solid tumours this entity occurs during treatment of nephroblastoma, rhabdomyosarcoma, and medulloblastoma. In the late 1990s SOS was quite often observed as the complication of oral 6-thioguanine (6-TG) in patients suffering from acute lymphoblastic leukaemia (ALL), who received 6-TG throughout maintenance. In current protocols, the syndrome has become uncommon because treatment with 6-TG is limited to two weeks of oral therapy. Here, we report a case of a nine-year-old boy with ALL, who developed sinusoidal obstruction syndrome shortly after completing the reinduction block of chemotherapy (cyclophosphamide, cytarabine, thioguanine) according to the ALL Intercontinental Berlin-Frankfurt-Münster 2009 (ALL IC BFM 2009) treatment protocol.